A Novel Cascade Benzyne Nucleophilic Addition/Fries Rearrangement for Entry into 2,3-Disubstituted Phenols - Bronner, Sarah M.; Lee, Daniel; Bacauanu, Vlad; Cyr, Patrick (Synlett, 2017)
A cascade benzyne Fries rearrangement is reported that offers facile access to 2,3-disubstituted phenols, allowing for two points of diversity on the benzyne adduct. The methodology utilizes an o-(trimethylsilyl)triflate phenol as a common intermediate, from which substitution of the phenolic oxygen readily yields benzyne precursors that undergo the requisite rearrangement in the presence of an amine nucleophile, base, and a fluoride source.
Keywords: benzyne; aryne; Fries rearrangement; reactive intermediate; silyltriflate